Investigating Students' Difficulties and Strategies in Writing Descriptive Text - Feti Dwijayanti; Widya Oktarini; Yeni Mardiana Devanti (JELP Journal of English Language and Pedagogy, 2025)
Writing is a crucial skill in English learning that requires students to effectively express their thoughts and ideas. However, many students struggle with writing descriptive texts due to difficulties in organizing ideas, vocabulary limitations, and grammatical errors. This research aims to investigate the difficulties faced by students in writing descriptive texts and the strategies they use to overcome them. Conducted at SMAN 4 Jember, this study focuses on students' challenges in content development, text organization, vocabulary selection, grammar usage, and writing mechanics. The research employs a qualitative descriptive method, using observation, interviews, and document as data collection methods. The findings indicate that students struggle with expanding their ideas, often providing only basic descriptions without sufficient details. Some include irrelevant or repetitive information to meet length requirements. In terms of organization, many students fail to distinguish between identification and description, leading to unclear paragraph structures. Vocabulary limitations are also evident, with frequent repetition of the same words and difficulty selecting appropriate adjectives. Grammar-related challenges include inconsistent verb tense usage and errors in subject-verb agreement. Additionally, students often make mechanical errors, such as incorrect capitalization, punctuation, and spelling. To address these issues, students use strategies such as referencing online materials, brainstorming, peer feedback, and utilizing AI-based writing tools. These findings provide valuable insights for improving instructional approaches in English writing.